Emotional Intellegence Dan Organizational Culture Untuk Meningkatkan Internal Service Performance Pada Karyawan Puskesmas Sidoarjo - Anggita Fitrianah Ramadhani; Amiartuti Kusmningtyas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine emotional intelligence and organizational culture to improve the internal service performance of Sidoarjo Health Center employees. There is a population needed in this research, namely 50 employees. In this study, researchers used all community health center employees, both paramedics and non-medical employees, with respondent characteristics based on age, gender, educational background, and length of work. Sampling In this research he author used a saturated sample where all members of the population were used as research samples.So this research uses a questionnaire filled out by respondents and used as data for this research. The analysis technique used is simple linear regression analysis. Hypothesis testing uses (a T-test), while the data analysis methods used include a validity Test and Reliability Test. The results of this research show that Emotional Intelligence and Organizational Culture influence Internal Service Performance. The result obtained t-count of 11.438 is greater than the t-table 2.01063 with a significant value of 0.000 > 0.50, which shows that the results are statistically significant. Furthermore, the emotional intelligence variable has a significant impact on internal service performance, with a t-count of 12.039, greater than the t-table 2.01063 with a significant value of 0.000 > 0.50.